Assessment of proliferation of squamous, Barrett's and gastric mucosa in patients with columnar lined Barrett's oesophagus. Issue 6 (June 1992) - Iftikhar, S Y; Steele, R J; Watson, S; James, P D; Dilks, K; Hardcastle, J D
Abstract : There is no satisfactory biomarker yet available for predicting the likelihood of premalignant changes or carcinoma developing in Barrett's or columnar lined oesophagus. In this study we have evaluated the proliferation of squamous epithelium, columnar epithelium from columnar lined oesophagus and gastric columnar epithelium from 23 Barrett's patients using positive immunoreactivity with the mouse monoclonal antibody Ki67 (which recognises an antigen associated with proliferative cells) with a view to using this parameter as a biomarker. Squamous epithelium had significantly higher Ki67 immunostaining as compared with columnar epithelium from columnar lined oesophagus (when examining the tissue with greater than 15% cells staining positive for Ki67, Fisher's exact test p = 0.004) but there was no difference found between the epithelium from the columnar lined oesophagus and gastric columnar epithelium. There was no correlation between histological inflammation and Ki67 immunoreactivity of Barrett's mucosa, and the Ki67 immunostaining of two patients with dysplasia was no different from the rest of the group. There was, however, a significant correlation between the Ki67 immunoreactivity of columnar epithelium from columnar lined oesophagus and columnar epithelium from the stomach (correlation coefficient = 0.44, p = 0.03) suggesting that epithelium from columnar lined oesophagus behaves in a similar fashion to gastric epithelium.